The emergent writing style of a 7 year old bilingual - Kuang, C.H. (2008)
As children develop from infancy to toddler and finally school-going age, they also acquire the ability to read and write whether through training or exposure. This paper focuses on the writing products of a young Malaysian bilingual who is well versed in Mandarin and English. From the analysis of his writings, it was found that many of his spellings were mis-spelt words which were not only original but were also based on the way words were articulated in his presence and also, as he understands them to be presented through the English letters/alphabets. Further analysis of his writings indicate that where he was incapacitated by a lack of vocabulary the child applies the strategy of borrowing from another language, in that process, using the means of code switching to accomplish what he wants to say.